1998
DOI: 10.2165/00019053-199814060-00004
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, Health-Related Quality of Life and Healthcare Resource Consumption

Abstract: Insomnia is significantly associated with reduced HR-QOL and increased healthcare resource use in enrollees of managed-care organisations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 7 publications
7
95
2
2
Order By: Relevance
“…In addition, these symptoms cannot be accounted for by another medical or psychiatric condition. Studies have begun to document a high degree of morbidity associated with insomnia including reductions in quality of life that are comparable to other chronic illnesses such as congestive heart failure and depression [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these symptoms cannot be accounted for by another medical or psychiatric condition. Studies have begun to document a high degree of morbidity associated with insomnia including reductions in quality of life that are comparable to other chronic illnesses such as congestive heart failure and depression [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who experience insomnia have been reported to have higher resource utilization, including emergency room visits, hospitalizations, and physician visits, when compared to those who do not experience insomnia. 9,13 The annual direct cost of insomnia is estimated to be approximately $14 billion in the United States.…”
Section: Population Health Managementmentioning
confidence: 99%
“…7 One study found that both mental health status and emotional dimensions of quality of life were lower among severe and mild insomniacs compared to those with no insomnia. 7 In a study of managed care enrollees by Hatoum et al, 9 those with insomnia reported significantly lower health-related quality 1 Consumer Health Sciences, Princeton, New Jersey (at time of writing). 2 Sanofi-Aventis, Bridgewater, New Jersey (at time of writing).…”
mentioning
confidence: 99%
“…If a primary care provider poses this question, there is roughly a 40% probability that the answer will be "not good" and will necessitate additional time-consuming exploration. 46 The process of taking a sleep history is often vexing because of night-by-night variability in sleep and because of one quality inherent to the sleep state-unconsciousness. In this era of increased pressure for productivity, the primary care provider may not have time to flesh out the subtleties of sleep behavior.…”
Section: What Are the Barriers To Screening For Insufficient Sleep/slmentioning
confidence: 99%